2020
DOI: 10.1002/pds.5000
|View full text |Cite
|
Sign up to set email alerts
|

No association between use of phosphodiesterase 5 inhibitors and colorectal cancer in men with erectile dysfunction

Abstract: PurposeThere is an increase interest on the potential chemoprotective effect of selective phosphodiesterase 5 (PDE5) inhibitors. Several authors have shown in vivo the immune‐mediated anti‐tumor effect of these inhibitors on tumors arising from the digestive tract.ObjectivesTo test the potential effect of selective PDE5 inhibitors against colorectal cancer (CRC) onset previously observed.MethodsWe used data from The Health Improvement Network database and identified an established cohort of 200 000 new users o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…However, omission of two relevant studies [22, 29], exclusion of subgroup analysis on primary and secondary prevention and lack of prospective PROSPERO registration of the previous meta‐analysis warranted the conduction of a more comprehensive review on this subject area. The protective effect of PDE5 inhibitors on CRC risk suggested in the present study contrasts with that reported by Soriano et al [36], who found that once the confounder of erectile dysfunction was accounted for no reduced risk of CRC was observed among users of PDE5 inhibitors. In contrast, Sutton et al studied a cohort of patients with erectile dysfunction and reported a lower hazard of CRC among those who had exposure to PDE5 inhibitors, suggesting that PDE5 inhibitor use is an independent protective variable in CRC incidence.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, omission of two relevant studies [22, 29], exclusion of subgroup analysis on primary and secondary prevention and lack of prospective PROSPERO registration of the previous meta‐analysis warranted the conduction of a more comprehensive review on this subject area. The protective effect of PDE5 inhibitors on CRC risk suggested in the present study contrasts with that reported by Soriano et al [36], who found that once the confounder of erectile dysfunction was accounted for no reduced risk of CRC was observed among users of PDE5 inhibitors. In contrast, Sutton et al studied a cohort of patients with erectile dysfunction and reported a lower hazard of CRC among those who had exposure to PDE5 inhibitors, suggesting that PDE5 inhibitor use is an independent protective variable in CRC incidence.…”
Section: Discussioncontrasting
confidence: 99%
“…All studies were published between 2016 and 2021. Study populations originated from the USA [25, 29], the UK [35, 36] and Sweden [22, 34]. There was 100% agreement between the two reviewers on review of the extracted data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations